PENGEMBANGAN PERANGKAT PEMBELAJARAN BERCIRIKAN PENEMUAN TERBIMBING PADA MATERI FUNGSI KUADRAT UNTUK SISWA SMK - Arini Rabbi Izzati; Gatot Muhsetyo; I Made Sulandra (Jurnal Kajian Pembelajaran Matematika, 2020)
This research development aims to produce a learning device characterized by valid guided discoveries. The development of learning tools refers to the Thiagarajan, Semmel, and Semmel (1974) model, which is the development of Four-D, which is modified into Three-D. This development model consists of 3 stages of development, namely define, desig, and develop. Assessment of the quality of learning tools in this study consisted of evaluating validity. Learning tools are said to be valid if according to the judgment of experts and practitioners have content validity and construct validity. From the development results obtained learning tools (learning media, lesson plans, and mastery test material) quadratic function material characterized by guided discoveries, can be categorized valid. Based on the results of the development of learning tools obtained that the learning tools (learning media, lesson plans, and mastery tests of materials) are categorized valid in a row that is 3.05; 3.1; 3.1 and have met the specified criteria.Keywords: development, learning tools, guided discovery, quadratic functions